Lung cancer screening, diagnosis, and treatment: The radiologist's perspective - Bingqing Long; Zeng Xiong; Manzo Habou (Meta-Radiology)
The epidemiological of lung cancer surgery patients is changing, resulting in changes in diagnosis and treatment. Changing the way and content of imaging reports in response to the above changes is necessary. This paper aims to review the problems involved in lung nodule screening, diagnosis, and treatment stages from the radiologist's perspective and suggest feasible solutions.